Folklore and Literacy: A View from Nova Scotia - Kozar, Seana (Ethnologies)

(untitled) (Association Canadienne d'Ethnologie et de Folklore, 2004)
AbstractThis article describes a pilot project in museum based literacy learning that took place in Windsor, Nova Scotia in the autumn of 1999. The author coordinated the project in close consultation with a local literacy practitioner. The Windsor study was part of a national project undertaken by the Canadian Museums Association and funded by a SSHRC Strategic Research Grant Initiative. The project attracted four female participants, although one left before completing her research for personal reasons. The women chose objects as topics for study, and were given assistance with research and documentation techniques. As a discourse involving traditions of expressive behaviour and worldview, folklore plays an important role in literacy education. Specifically, this discussion examines the interactions between the participants, their chosen topics, and the museum environments, and underscores the need for an understanding of value, class, gender and contexts of use in an appreciation of literacy. A review of relevant literature is included, focusing on ethnographic studies of literacy with particular emphasis on recent work in Atlantic Canada. Outcomes of the study and future directions for this kind of community based, qualitative research are also discussed.